(untitled) (Latakia University Journal -Basic Sciences Series, 2023)
This study aimed to determine the natural estrogen 17β-estradiol (17β-E2) and its synthetic derivative 17α-ethinyl estradiol (17α-EE2) in samples of raw cow’s milk during three gestational periods (first trimester, second trimester and third trimester) for comparison with Raw cow’s milk (without lamb). RP-HPLC method was used on a C18 column and isocratic elution system with a mobile phase (acetonitrile: water 55:45 v/v). The extraction was accomplished by using acetonitrile and ultrasonic device. The measurements were made after the ideal conditions for chromatographic separation were achieved and with it the two compounds E2 and EE2 of the samples were separated with high selectivity (α=1.157) and sufficient resolution (Rs=1.543) within 7 min. The analytical results obtained LOD and LOQ limit values for compound E2 and compound EE2 and were (0.0321, 0.1070) ng/ml, (0.0032, 0.0106) ng/ml, respectively, with recovery (98.35±18.85%) of compound E2 and (108.6±14.6%) of compound EE2. The results showed that milk content of natural estrogen E2 in the second and third trimesters samples was (40.458 ± 0.748) ng/L, and that is higher than the contents of the first trimester samples of pregnancy and non-pregnant, which is (19,519 ± 2.300) ng/L, while its contents of synthetic estrogen EE2 in the samples of the second and third trimester of pregnancy was (3.8345 ± 0.4775) ng/L, and that is lower than the contents of the first trimester samples of pregnancy and non-pregnant, which is (9.9805±0.5585)ng/L.